EVOLUTION OF POLITICAL CULTURE IN CHILE AFTER THE CIVIL REVOLUTION OF 1990: DYNAMICS AND CONTINUITY - N. S. Aniskevich (Концепт: философия, религия, культура, 2017)
The article analyzes the events being the result of the 1990 civil revolution which influenced the paradigm shift of the country’s political culture. The author examines the period of Pinochet’s military government in power and makes value judgements about it, focusing on the influence exerted by the general on society. The interpretation of the term “historical politics” (or “politics of memory”) is analyzed in the context of the new political culture formation, which resulted from returning to democratic principles. The actions taken by the new governments to eradicate the legacies of the past are investigated. Right-wing and center-left governments’ actions, undertaken to modernize the country are compared. This work depicts the relationship between the civil revolution and the political and cultural components of Chile’s life at the turn of the 20th and 21st centuries. It was cultural values and historical experience that had a direct impact on the governmental decision-making. The study shows that today Chilean society has become open, free and rapidly developing in the modern globalizing world, being significantly different from the one before the civil revolution of 1990.